Current and potential therapeutic strategies for transthyretin cardiac amyloidosis - Williams, Marcus A. C.; Shankar, Bairavi; Vaishnav, Joban; Ranek, Mark J. (Frontiers in Drug Discovery, 2022)
Cardiac amyloidosis is a progressive disorder caused by the deposition of amyloid, abnormal proteins that aggregate to form insoluble plaques, in the myocardium resulting in a restrictive cardiomyopathy. The two most common subtypes of cardiac amyloidosis include immunoglobulin light chain (AL) and transthyretin (TTR) amyloid cardiomyopathy (ATTR-CM). ATTR-CM can further be subdivided into two main categories, wild type or hereditary TTR. TTR is a homotetrameric protein complex that is synthesized in the liver and is secreted into the circulation for retinol and vitamin A transfer. Genetic mutations in the TTR gene can disrupt the thermodynamic stability of the homotetrameric complex causing dissociation into monomers, that when taken up by the myocardium, will aggregate to form insoluble fibers. Though the mechanism of wild type TTR is not fully elucidated, it is thought to be an age-related process. Myocardial uptake and aggregation of TTR monomeric subunits results in cytotoxicity, impaired cardiac function, and eventually heart failure. Historically, ATTR-CM had a poor prognosis; with no therapeutics available to specifically target ATTR-CM and treatment focused on managing symptoms and disease-related complications. In 2019 the FDA approved the first in class TTR stabilizer for ATTR-CM, which has led to improved outcomes, however limitations remain. In recent years, several promising novel therapies have emerged which aim to target various points of the ATTR-CM amyloidogenic cascade. In this review, we discuss the mechanistic underpinnings of ATTR-CM, review current FDA-approved strategies for treatment, and highlight ongoing research efforts as potential therapeutic options in the future.